CREATIVE PROBLEM SOLVING (CPS)-BASED ASSESSMENT INSTRUMENT FOR CRITICAL THINKING ABILITY ON STOICHIOMETRY MATERIALS - Agustini Agustini; R. Usman Rery; Lenny Anwar (AL-ISHLAH: Jurnal Pendidikan, 2020)
TThe purpose of this study is to design Creative Problem Solving (CPS)-based assessment instrument for critical thinking ability on stoichiometry materials. The method of development utilized in this study is Research and Development (RD) adapted from Borg Gall Model which consists of 10 development steps. However, In this study, only up to the third stage, namely the initial product development stage of the assessment instrument for the critical thinking ability of students based on CPS on Stoichiometric material. The main target in the final result of this research is to design a valid CPS-based critical thinking ability assessment instrument on Stoichiometry material that is valid so that it is suitable for use. The assessment instrument developed produced 10 items which were declared valid and reliable with a reliability price of 0.749. The CPS-based critical thinking ability assessment instrument provides more comprehensive information about the characteristics of the instrument that has been developed.